2022
DOI: 10.1039/d1cb00196e
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase inhibitors: where we are now

Abstract: Protein lysine methyltransferases constitute a large family of epigenetic writers which catalyse the transfer of a methyl group from the cofactor S-adenosyl-L-methionine to histone and non-histone specific substrates. Alterations in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 317 publications
(500 reference statements)
1
24
0
Order By: Relevance
“…Through the docking study of EPZ-6438 and EZH2, we found that electron-rich cysteine was near the side-chain benzene of EPZ-6438, which was consistent with previous study by Brooun et al , It was expected to form a covalent bond with Cys663 by modifying the covalent reactive group on the benzene side chain (orange part) (Figure ). Acrylamide would be used as the covalent reactive group in this study because it was the most widely used, and its safety has been validated in clinical studies.…”
Section: Resultssupporting
confidence: 90%
“…Through the docking study of EPZ-6438 and EZH2, we found that electron-rich cysteine was near the side-chain benzene of EPZ-6438, which was consistent with previous study by Brooun et al , It was expected to form a covalent bond with Cys663 by modifying the covalent reactive group on the benzene side chain (orange part) (Figure ). Acrylamide would be used as the covalent reactive group in this study because it was the most widely used, and its safety has been validated in clinical studies.…”
Section: Resultssupporting
confidence: 90%
“…The selectivity of compound 12h was further assessed against a panel of eight lysine methyltransferases (KMTs), including the SET-domain-containing proteins ASH1L/KMT2H, EZH2/KMT6, MLL1/KMT2A, SET7/9/KMT7, SETD8/KMT5A, SUV39H2/KMT1B, and SUV420H1/KMT5B and the non-SET-domain-containing DOT1L/KMT4. 77 To this aim, the inhibition of 12h toward these selected enzymes was assessed at two different concentrations (1 and 10 μM, respectively, >300 and >3000 fold higher than the IC 50 value against PRMT4) using SAH, 78 80 chaetocin (for ASH1L), 81 or ryuvidine (for SETD8) 82 as reference compounds. Noteworthy, we found that none of the enzymes was inhibited by 12h even at the higher tested concentration (Figure S2 and Table S1, Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…mp 95−97 °C. 1 (14). A solution of intermediate 13 1.0 g (2.80 mmol), 3-(aminomethyl)-4,6dimethylpyridin-2(1H)-one 0.46 g (3.00 mmol), K 2 CO 3 1.14 g (8.4 mmol), and DMF (2 mL) was degassed and purged with Ar 3 times, and the mixture was stirred at 70 °C for 10 h. Then, the reaction mixture was poured into water (20 mL) and filtered to give intermediate 14 (1.1 g) as a pale yellow solid, yield 85%.…”
Section: 4-dichloro-6-methoxy-7-(3-(pyrrolidin-1-yl)propoxy)-quinazol...mentioning
confidence: 99%
“…13 A variety of PRC2 inhibitors have been described, including both the EZH2 catalytic domain inhibitors, EZH2 degraders, EED inhibitors, EZH2-EED inhibitors, and so on. 14 To avoid ambiguity, EZH2 inhibitors in this work specifically refer to EZH2 catalytic inhibitors. EZH2i tazemetostat (also known as EPZ-6438) has been approved for the treatment of locally advanced or metastatic epithelioid sarcoma and follicular lymphoma in the USA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation